2018
DOI: 10.3390/biomedicines6030086
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Medical Treatments for Meningioma in the Molecular Era

Abstract: Meningiomas are the most common type of primary central nervous system tumors. Approximately, 80% of meningiomas are classified by the World Health Organization (WHO) as grade I, and 20% of these tumors are grade II and III, considered high-grade meningiomas (HGMs). Clinical control of HGMs, as well as meningiomas that relapse after surgery, and radiation therapy is difficult, and novel therapeutic approaches are necessary. However, traditional chemotherapies, interferons, hormonal therapies, and other targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 166 publications
0
44
0
2
Order By: Relevance
“…Combining global and targeted patient-derived data is a novel approach and it has the potential to provide cues regarding the meningioma pathobiology which can be useful in longitudinal studies for monitoring the patient prognosis. While inhibitory studies against FAK, mTOR, and Akt components in meningioma patients are ongoing ( 38 ); our study provides mechanistic insights on how components of Cytoskeletal regulators, PI3K-Akt, mTOR, and NFκB can be targeted using a single molecule namely the Cpd22 which was able to downplay these components in meningioma primaries. We also lay the foundation for the use of targeted proteomics for validation of key proteins directly from the patient cohort which if integrated with existing modalities of diagnosis and treatment can aid in enhanced patient management.…”
Section: Discussionmentioning
confidence: 94%
“…Combining global and targeted patient-derived data is a novel approach and it has the potential to provide cues regarding the meningioma pathobiology which can be useful in longitudinal studies for monitoring the patient prognosis. While inhibitory studies against FAK, mTOR, and Akt components in meningioma patients are ongoing ( 38 ); our study provides mechanistic insights on how components of Cytoskeletal regulators, PI3K-Akt, mTOR, and NFκB can be targeted using a single molecule namely the Cpd22 which was able to downplay these components in meningioma primaries. We also lay the foundation for the use of targeted proteomics for validation of key proteins directly from the patient cohort which if integrated with existing modalities of diagnosis and treatment can aid in enhanced patient management.…”
Section: Discussionmentioning
confidence: 94%
“…With recent advancements in genetic sequencing, there is increasing knowledge regarding specific oncogenic pathways involved in various meningioma subtypes, allowing for the design of new targeted therapies based on tumor's molecular profile. 55 Skull base meningiomas in particular have been found to have high rates of mutation in the AKT (Protein kinase B) pathway, which is critically involved in tumor growth and chemotherapy resistance. A clinical trial began in 2015 that is investigating the role of an AKT1 inhibitor (Afuresertib), which is one of the first meningioma trials initiated that targets mutations identified with next-generation sequencing.…”
Section: Chemotherapy and Molecular Therapymentioning
confidence: 99%
“…NF2 is mutated in neurofibromatosis type II, a familiar tumor predisposition syndrome where up to 70% of patients develop meningiomas [24]. In animal models, NF2 mutations have also been shown to drive tumorigenesis [38, 41]. Further, exposure to radiation therapy, a known risk factor for meningioma development, has been shown to drive structural aberrations in NF2 [1].…”
Section: Introductionmentioning
confidence: 99%